The ethical and legal regulation of human tissue and biobank research in Europe - Proceedings of the Tiss.EU Project (Universitätsverlag Göttingen, 2021)
Human tissue and biobank research is of increasing importance for understanding the causes of widespread diseases and developing effective therapies. However, while the success of biobank research depends on the availability of a large number of samples and the consolidation of collections across country borders is very desirable from the perspective of researchers, the legal and ethical requirements for the procurement, storage and use of human tissue samples are rather heterogeneous across different countries. Moreover, the lack of comprehensive supranational regulation on human tissue and biobanking can be seen as posing a serious threat to transnational biomedical research. Against this background, it was one of the aims of the EU-funded Tiss.EU project (“Evaluation of Legislation and Related Guidelines on the Procurement, Storage and Transfer of Human Tissues and Cells in the European Union – an Evidence-Based Impact Analysis”) to analyse the ethical and legal regulation of human tissue and biobank research across the 27 European Member States plus Switzerland. The results of nine international workshops and three conferences are gathered in this volume. While the country reports evaluate the implementation of ethical and legal guidelines at a national level, point out their strengths and deficits, and, where required, create an evidence base for the revision of said legislation, the conference reports address more general ethical and legal issues in this field. The volume is completed by a final presentation of project’s results.